Comparative trypanotolerance of the Small East African breed of goats from different localities to Trypanosoma congolense infection - Mutayoba, B.M.; Gombe, S.; Waindi, E.N.; Kaaya, G.P. (Elsevier, 1989)
Differences in susceptibility of the Small East African breed of goats to an experimental Trypanosoma congolense infection were investigated. The goats were obtained from different areas of East Africa, Morogoro and Arusha (Tanzania), Imbo and Lambwe Valley (Kenya). Morogoro goats were found to be more tolerant, followed by Arusha, Lambwe Valley and Imbo goats, in that order. The Imbo goats had highest parasitaemia, more severe anaemia, marked weight losses and highest mortality rate. The Morogoro goats showed a milder infection with lower parasitaemia, less severe anaemia, weight losses and lowest mortality rate. The Lambwe Valley and Arusha goats were intermediate to the Morogoro (resistant) and Imbo (susceptible) goats. The significance of these findings in relation to existence of heterogeneity in the Small East African goats is discussed.